Baterial pathogenesis : - Salyers, Abigail A. (ASM Press, 2002)
Bacterial Pathogenesis: A Molecular Approach is the first text designed to provide a comprehensive introduction to this dynamic field for both students and researchers. The application of molecular techniques to the study of bacterium-host interaction has made possible great progress in fundamental understanding of the molecular basis of infectious diseases